2021
DOI: 10.1108/rbf-08-2021-0150
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion and digital banking on an emergent economy

Abstract: PurposeTo analyze financial inclusion through digital banking in order to identify how digital banking is including or excluding different types of populations in an emergent economy.Design/methodology/approachChi-square statistical tests were conducted to test the relationship between demographic variables (i.e. gender, region, locality and age) with having a digital banking account, types of services and reasons for not using them. As an example of an emergent economy, the Mexican Financial Inclusion Survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…A study on DB in emerging economies found that acceptance of these services varies significantly among different populations, particularly in regions with varying welfare levels. The study revealed that less fortunate regions have limited access to DB, and in some cases, there was a significant disparity between men's and women's capability to use these services [172]. Therefore, the identification of suitable indicators for the implementation of DB will be different in various conditions, and the need for comprehensive evaluation is felt.…”
Section: Ranking Of Alternatives According To the Importance Of Criteriamentioning
confidence: 99%
“…A study on DB in emerging economies found that acceptance of these services varies significantly among different populations, particularly in regions with varying welfare levels. The study revealed that less fortunate regions have limited access to DB, and in some cases, there was a significant disparity between men's and women's capability to use these services [172]. Therefore, the identification of suitable indicators for the implementation of DB will be different in various conditions, and the need for comprehensive evaluation is felt.…”
Section: Ranking Of Alternatives According To the Importance Of Criteriamentioning
confidence: 99%
“…One of the most pressing issues is the digital divide, where significant segments of the population lack access to necessary digital infrastructure, such as reliable internet connectivity and digital literacy. This gap hinders the potential reach and impact of digital financial services (Guerra-Leal et al, 2021). Additionally, concerns regarding privacy, security, and the risk of fraud have also emerged as critical challenges.…”
Section: Overview Of the Successes Achieved And Challenges Faced In L...mentioning
confidence: 99%
“…These factors significantly influence the adoption rates of digital banking services, especially among more vulnerable populations who may be more susceptible to these risks . Furthermore, there is a notable gender gap in digital banking inclusion, with women being more excluded than men from accessing digital banking accounts (Guerra-Leal et al, 2021). Addressing this gender disparity is crucial for achieving equitable financial inclusion.…”
Section: Overview Of the Successes Achieved And Challenges Faced In L...mentioning
confidence: 99%
“…Gender equality in access to credit and financial stability (Perrin y Weill, 2022) Gender and financial inclusion: does technology make a difference? (Ghosh, 2022) The role of education in filling the gender gap in financial inclusion in low-income economies (Pahlevan et al, 2022) Narrowing the gender gap in mobile banking (Lee et al, 2022) Digital credit and the gender gap in financial inclusion: Empirical evidence from Kenya (Johnen y Mußhoff, 2022) Financial inclusion and digital banking on an emergent economy (Guerra-Leal et al, 2021) Formal credit usage and gender income gap: the case of farmers in Cambodia (Sam, 2021) Sex, language and financial inclusion (Osei-Tutu y Weill, 2021) Gender disparity in the digitalization of financial services: challenges and promises for women's financial inclusion in India (Kulkarni y Ghosh, 2021) The effect of financial literacy and gender on retirement planning among young adults (García, 2021) Financial kiteracy and intra-household decision making: Evidence from Rwanda (Grohmann et al, 2021) Financial literacy: Thai middle-class women do not lag behind (Grohmann et al, 2021) Stereotypes in financial literacy: Evidence from PISA (Bottazzi y Lusardi, 2021) Gender differences in financial literacy: The role of stereotype threat (Tinghög et al, 2021) Financial literacy among Finnish adolescents in PISA 2018: The role of financial learning and dispositional factors (Silinskas et al, 2021) The financial literacy gender gap and the role of culture (Rink et al, 2021) Gender differences in risky asset behavior: The importance of self-confidence and financial literacy (Cupák et al, 2021) What is good for the goose is good for the gander? : How gender-specific conceptual frames affect financial participation and decision-making (Boggio et al, 2020) Gender income gap in rural informal micro-enterprises: An unconditional quantile decomposition approach in the handloom industry (Hazarika, 2020) Gender differences in financial knowledge, attitudes, and behaviors: Accounting for socioeconomic disparities and psychological traits (Robson y Peetz, 2020) Measuring economic competence of secondary school students in Germany (Kaiser et al, 2020) The interaction effect of gender and ethnicity in loan approval: A Bayesian estimation with data from a laboratory field experiment (Gonzales Martínez et al, 2020) Access to finance -Mind the gender gap (Morsy, 2020) Early causes of financial disquiet and the gender gap in financial literacy: Evidence from College students in the Southeastern United States (Al-Bahrani et al, 2020) Determinants of digital finance in India (Ghosh y Hom, 2020) Does gender...…”
Section: Scopusmentioning
confidence: 99%